The future of diversity - Kuptsch, Christiane; Charest, Éric (International Labour Organization, 2021)
In this collection, scholars and practitioners reflect on the most appropriate interventions to create a more inclusive labour market for all. They explore the economic case for diversity and diversity management strategies, finding that diversity and inclusion must go hand in hand. The book also sheds light on the policy dilemma between respecting individuals and countering structural inequalities, which often requires categorization into groups. The authors remind us that there is diversity within diversity: not everyone receiving the same label has the same needs. The book covers a range of issues including gender equality and mainstreaming, migration and ethnic diversity, racism, violence against LGBTI people and age discrimination. It is thus a rich source of inspiration for anyone wishing to move towards greater justice in the labour market.
Keywords: approches et analyses; discipline; identités LGBTQIA2+; inégalités; justice sociale; racisme; rapport; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie